Organisational Knowledge, Intangible Resources And Business Performance - Rodriguez-Castellanos, Arturo; García-Merino, Jose Domingo; García-Zambrano, Lidia (Journal of Knowledge Management Practice, 2011)
Organisational knowledge, the sole source of sustainable competitive advantage, is embodied in companies as intellectual capital, that is, the set of intangibles based on knowledge. And special mention should be made of core competencies as they are the basis of competitive advantage and, therefore, the fundamental source of business value. This paper seeks to test the existence of positive links between core competencies –grouped according to the dimensions of intellectual capital (Human Capital, Structural Capital and Relational Capital)– and business performance. A survey was conducted among a representative sample of business managers in the Basque Country (Spain). With this information, and business performance data for 2007 and 2008 obtained from the SABI database, non-parametric contrasts were performed. The results show a positive and significant link of the ROA with the competencies linked to Human Capital in 2007 and 2008, and equally for 2008 with the competencies linked to Relational Capital.
Keywords: knowledge management; Organisational knowledge; Intangible resources; Intellectual capital; Core competencies